A COMPARATIVE STUDY OF DIRECT AND COMMUNICATE METHODS IN EFL CLASSROOM - Bazarov Zokir Mekhrikulovich (Bright Mind Publishing, 2025)
The Direct Method and Communicative Language Teaching (CLT) approaches in English as Foreign Language (EFL) classrooms are compared in this article. It looks at their theoretical underpinnings, classroom uses, benefits, and drawbacks. The study illustrates how each approach promotes various facets of language acquisition by drawing on prior research and actual classroom observations. CLT places more emphasis on interaction and communicative ability than the Direct Method, which uses target language immersion to stress vocabulary and grammar. Suggestions for combining the two approaches for more successful EFL training are included in the article's conclusion.